Is State Licensure Enough? Evaluating the Gaps and Proposing a Specialized Credentialing Model for Aesthetic Medical Practice in Indonesia - Yeo, Susilo Kurniawan; Harjono, Dhaniswara K; Pieris, John; Panjaitan, Hulman (Journal of Law, Politic and Humanities, 2025)
This study examines the weaknesses of the regulatory framework for aesthetic medical practice in Indonesia, which have led to a public health crisis due to malpractice by incompetent practitioners. The objective of this research is to design a specialized credentialing model to ensure patient safety and legal certainty. Using a normative legal research methodology through statutory, comparative, and conceptual approaches, this study analyzes the regulatory systems in Indonesia, Malaysia, and Singapore. The results show that Indonesia, relying solely on general medical licenses (STR and SIP), operates in a regulatory vacuum. In contrast, Malaysia, with its Letter of Credentialing and Privileging (LCP) system, and Singapore, with its Certificate of Competence (COC), have successfully implemented frameworks focused on procedural competency. As a solution, a hybrid model is proposed for Indonesia, the "Aesthetic Competency Certificate", which combines evidence-based risk stratification from Singapore and the renewable privileging mechanism from Malaysia. This model would be managed by a national committee, mandate standardized training, and be supported by a public registry to ensure accountability and protect the public.